2010
DOI: 10.1039/c001464h
|View full text |Cite
|
Sign up to set email alerts
|

New amino acid ligated yttrium hydroxy clusters

Abstract: The synthesis of the four mixed pentanuclear yttrium hydroxy clusters [Y(5)(OH)(5)(alpha-AA)(4)(Ph(2)acac)(6)] (alpha-AA = D-phenyl glycine, L-proline, L-valine, and L-tryptophan; Ph(2)acac = dibenzoylmethanide) is reported. The solid state structures of all compounds were established by single crystal X-ray diffraction. In these enantiomerically pure chiral clusters the dibenzoylmethanide and amino acid ligands are accommodated in the coordination spheres of the yttrium atoms. The specific optical rotations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…100 However, it is quite often used for the characterization of supramolecular complexes. Actually, there is a relationship between the diffusion coefficient D (m 2 s −1 ) and the molecular weight MW (g mol −1 ): 101…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…100 However, it is quite often used for the characterization of supramolecular complexes. Actually, there is a relationship between the diffusion coefficient D (m 2 s −1 ) and the molecular weight MW (g mol −1 ): 101…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[21] As mentioned above, in our group we aimed to enhance the biological compatibility of our cluster compounds by functionalization of the clusters' ligand shells with amino acids to obtain the mixed dibenzoylmethanide and amino acid clusters [Ln 5 (OH) 5 (α-AA) 4 (Ph 2 acac) 6 ] (Ln = Y, Dy); see Figure 7. [69,75] The next step to enhancing the biocompatibility of our cluster compounds involved the synthesis of rare-earth metalbased clusters with luminescent properties for penetration of living cells. To achieve this goal, the anchoring of a cell-penetrating agent onto a rare-earth cluster core is necessary.…”
Section: Properties and Applications Of The Pentanuclear Clustersmentioning
confidence: 99%
“…Inspired by earlier work by Zheng et al [25] it was shown that pentanuclear rare-earth clusters [Ln 5 (OH) 5 (α-AA) 4 (Ph 2 acac) 6 ] (Ln = Y, Dy) were obtained by treatment with dibenzoylmethane and the corresponding amino acid (α-AAH) in the presence of potassium tert-butoxide as base (Scheme 6). [69,75] As amino acids, 4 ]. [69] Hydrogen atoms and free solvent molecules are omitted for clarity.…”
Section: Functionalized Pentanuclear Clustersmentioning
confidence: 99%
See 2 more Smart Citations